A supervised learning framework for pancreatic islet segmentation with multi‐scale color‐texture features and rolling guidance filters. Issue 10 (25th August 2016) - Huang, Yue; Liu, Chi; Eisses, John F.; Husain, Sohail Z.; Rohde, Gustavo K.
Abstract: Islet cell quantification and function is important for developing novel therapeutic interventions for diabetes. Existing methods of pancreatic islet segmentation in histopathological images depend strongly on cell/nuclei detection, and thus are limited due to a wide variance in the appearance of pancreatic islets. In this paper, we propose a supervised learning pipeline to segment pancreatic islets in histopathological images, which does not require cell detection. The proposed framework firstly partitions images into superpixels, and then extracts multi‐scale color‐texture features from each superpixel and processes these features using rolling guidance filters, in order to simultaneously reduce inter‐class ambiguity and intra‐class variation. Finally, a linear support vector machine (SVM) is trained and applied to segment the testing images. A total of 23 hematoxylin‐and‐eosin‐stained histopathological images with pancreatic islets are used for verifying the framework. With an average accuracy of 95%, training time of 20 min and testing time of 1 min per image, the proposed framework outperforms existing approaches with better segmentation performance and lower computational cost. © 2016 International Society for Advancement of Cytometry